Efektivitas Penerapan Pidana Tambahan Uang Pengganti dalam Perspektif Hukum Normatif: Antara Teori dan Praktik Penegakan Hukum - Tobi Haryadi (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
The eradication of corruption cannot rely solely on repressive measures, as the recovery of state financial losses through additional penalties of compensation remains ineffective. The amount of loss suffered by the state is disproportionate to the value successfully restored. Major obstacles include lengthy payment processes, asset seizures of convicted persons, and complex bureaucratic procedures. Through normative juridical research, this study reveals that the recovery mechanism often requires a long period, even after the court’s decision has obtained permanent legal force. Therefore, regulatory improvements and more effective execution mechanisms are necessary to ensure that additional penalties of compensation truly function as an instrument for restoring state finances lost to corruption.